PERAN DOA BERSAMA DALAM KELUARGA KATOLIK UNTUK MENGEMBANGKAN IMAN ANAK DI LINGKUNGAN SANTO YUSUP PAROKI SANTO YUSUP BINTARAN YOGYAKARTA - Sumantri, Damiana Reanita; Rukiyanto, Bernardus Agus (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2024)
This study aims to determine the views of Catholic families regarding the role of joint prayer, to find out the supporting and inhibiting factors in carrying out joint prayer, and to find out what efforts can be implemented to increase the activity and awareness of the implementation of joint prayer in Catholic families to develop children's faith in the Saint Joseph Parish Bintaran. The main problem of this paper is the extent to which the implementation of joint prayer in Catholic families in the Saint Joseph's Neighborhood is neglected because it is difficult to divide the time because both parents are busy with work. In connection with this main problem, the writer is interested in writing this thesis with the hope that it can help Catholic families to increase their activity and awareness of the implementation of joint prayer. To study the main issues, the authors conducted observations and interviews with parents as resource persons, children and the head of the Santo Yusup neighborhood as validators to obtain data. The results of the research in this paper are that there are still a number of Catholic families who neglect the implementation of prayer along with busyness due to work, laziness and low awareness of inviting to pray together. Realizing this, efforts are needed to increase the activity and awareness of the implementation of joint prayer in Catholic families to develop children's faith. With suggestions from sources, the authors suggest family catechism activities using the Shared Christian Praxis (SCP) model. Through family catechesis with the SCP model, it is hoped that it will become a means for young families and young people to become more aware of being more active in carrying out joint prayers in the family. Collective Prayer in Catholic Families